The Indonesian Council Ulama (MUI) and Religious Discourse In Indonesia - Achmad, Mukhsin (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
This paper wants to explore the existence and role of the Indonesian Ulema Council (MUI) in religious discourse and practice in Indonesia. This research is library research using the theory of Critical Discourse Analysis by Norman Fairclough. The approach of this research is the political approach of Islamic law in Indonesia. Results This study found research findings related to the existence and role of MUI in the process of forming Islamic discourse in Indonesia. The MUI was designed by the government of the New Order Era as a medium of communication between the government and the ulama. The position of MUI in this era is more dominant in its role as